The Effects of Physical Activity on Physeal and Skeletal Development. Issue 10 (October 2021) - Carsen, Sasha; Grammatopoulos, George; Zaltz, Ira; Ward, Leanne; Smit, Kevin; Beaulé, Paul E.
Abstract : There is increasing evidence in the literature regarding the important health impact of and risk factors for injury in youth sport. Increasing pediatric and adolescent activity intensity, such as is seen in earlier single-sport focus and specialization, may be associated with morphological changes in the growing skeleton. Chronic subacute injury to the developing physes in the active child can lead to stress on the growth plate and surrounding tissues that induces developmental morphological changes in the joint. There is evidence to suggest that frequent participation in sports that place particular stress across the physes of the proximal humerus, the proximal femur, and the distal radius can be associated with an increased risk of inducing developmental and morphological changes that could lead to future joint dysfunction and premature degeneration. Additional research is necessary to better define the pathoetiology of activity-mediated morphological changes, as well as to create and validate parameters for safe involvement in competitive physical activities.